A NOVEL FLOATING SOLUTION FOR MARGINAL FIELDS IN CHALLENGING OIL ECONOMICS - SALEH MOHAMMED AL-AQEL, ABDULLAH (IRC, 2016)
This report demonstrates the hydrodynamic time responses of a tanker hull and a service vessel hull to be then converted to an FPSO for the use of the shallow water marginal fields in Malaysia. Detailed analysis and feasibility check have been conducted as well as sea-keeping analysis for the developed two models. The tanker hull has shown a better sea-keeping results compared to the service vessel hull. These preliminary sea-keeping simulations of the developed concept via industrially accepted software called “ANSYS Aqwa”. This develops a novel floating solution to unlock and bring back the interest on the marginal fields in shallow water. Options have been generated with the respect to the sea-keeping and sea-performance in 6 degrees of freedom.